Comparing the reliability of muscle oxygen saturation with common performance and physiological markers across cycling exercise intensity - Yogev, Assaf; Arnold, Jem; Nelson, Hannah; Clarke, David C.; Guenette, Jordan A.; Sporer, Ben C.; Koehle, Michael S. (Frontiers in Sports and Active Living, 2023)
Introduction Wearable near-infrared spectroscopy (NIRS) measurements of muscle oxygen saturation (SmO2) demonstrated good test–retest reliability at rest. We hypothesized SmO2 measured with the Moxy monitor at the vastus lateralis (VL) would demonstrate good reliability across intensities. For relative reliability, SmO2 will be lower than volume of oxygen consumption (V̇O2) and heart rate (HR), higher than concentration of blood lactate accumulation ([BLa]) and rating of perceived exertion (RPE). We aimed to estimate the reliability of SmO2 and common physiological measures across exercise intensities, as well as to quantify within-participant agreement between sessions. Methods Twenty-one trained cyclists completed two trials of an incremental multi-stage cycling test with 5 min constant workload steps starting at 1.0 watt per kg bodyweight (W·kg−1) and increasing by 0.5 W kg−1 per step, separated by 1 min passive recovery intervals until maximal task tolerance. SmO2, HR, V̇O2, [BLa], and RPE were recorded for each stage. Continuous measures were averaged over the final 60 s of each stage. Relative reliability at the lowest, median, and highest work stages was quantified as intraclass correlation coefficient (ICC). Absolute reliability and within-subject agreement were quantified as standard error of the measurement (SEM) and minimum detectable change (MDC). Results Comparisons between trials showed no significant differences within each exercise intensity for all outcome variables. ICC for SmO2 was 0.81–0.90 across exercise intensity. ICC for HR, V̇O2, [BLa], and RPE were 0.87–0.92, 0.73–0.97, 0.44–0.74, 0.29–0.70, respectively. SEM (95% CI) for SmO2 was 5 (3–7), 6 (4–9), and 7 (5–10)%, and MDC was 12%, 16%, and 18%. Discussion Our results demonstrate good-to-excellent test-retest reliability for SmO2 across intensity during an incremental multi-stage cycling test. V̇O2 and HR had excellent reliability, higher than SmO2. [BLa] and RPE had lower reliability than SmO2. Muscle oxygen saturation measured by wearable NIRS was found to have similar reliability to V̇O2 and HR, and higher than [BLa] and RPE across exercise intensity, suggesting that it is appropriate for everyday use as a non-invasive method of monitoring internal load alongside other metrics.